Soon

Beamed Equations


Observe the equations:

x4 - 13x2 + 36 = 0

9x4 - 13x2 + 4 = 0

x4 - 5x2 + 6 = 0

Note that the first members are 4th degree polynomials in variable x, having a term in x4, a term in x2 and a constant term. The second members are null.

We call these equations of square equations.

That is, the equation with a variable x is every equation of the form:

ax4 + bx2 + c = 0

Examples:

x4 - 5x2 + 4 = 0

x4 - 8x2 = 0

3x4 - 27 = 0

Caution!

The equations below they are not because in a square equation the variable x has only even exponents.

x4 - 2x3 + x2 + 1 = 0
6x4 + 2x3 - 2x = 0
x4 - 3x = 0

Next: Solving a Bampled Equation